Building Awareness about Multicultural Society through Da’wa bi al-Hikmah - Pimay, Awaludin (Lentera: Jurnal Ilmu Dakwah dan Komunikasi, 2022)
Indonesian society exhibits a high level of complexity in terms of diversity, comprising numerous islands with diverse cultures, races, regional languages, ethnic groups, religions, and beliefs. This characteristic has earned Indonesia the distinction of being recognized as one of the world's largest multicultural countries. Given this context, it is unsurprising that conflicts between races, ethnicities, and religions frequently arise. Consequently, as Indonesian residents, it becomes imperative for Muslims to contemplate potential solutions. This study endeavors to address two primary research questions: 1) What is the depiction of a multicultural society as fostered by Prophet Muhammad? 2) What are the manifestations of da'wah bi al-ḥikmah (wisdom-driven propagation of Islam) undertaken by Prophet Muhammad? The research employs a qualitative approach, specifically relying on library research methods. The findings of this study reveal that 1) Prophet Muhammad laid the foundation for a society characterized by multicultural awareness, exemplified through the cultivation of religious tolerance, mutual respect for diversity, including ethnic disparities and social statuses, and the promotion of unity and brotherhood among individuals. 2) The forms of da'wah bi al-ḥikmah employed by Prophet Muhammad in nurturing multicultural awareness within society were rational-psychological in nature. The Prophet skillfully engaged in dialogical and interactive communication with his companions (ummah), imparting understanding, awareness, setting good examples (uswatun hasanah), and even extending forgiveness to those who sought his pardon or absolution.